Growth differentiation factor‐15 is independently associated with metabolic syndrome and hyperglycemia in non‐elderly subjects - Ho, Li‐Chung; Wu, Hung‐Tsung; Hung, Hao‐Chang; Chou, Hsuan‐Wen; Cheng, Kai‐Pi; Lin, Ching‐Han; Wang, Chih‐Chen; Ou, Horng‐Yih (BioFactors (Oxford), 2023)
Metabolic syndrome (MetS) is a major health issue worldwide accompanied by cardiovascular comorbidities. Growth differentiation factor‐15 (GDF‐15) is a stress‐responsive cytokine expressed in cardiomyocytes, adipocytes, macrophages, and endothelial cells. Previous research in elderly subjects revealed that GDF‐15 levels were associated with the MetS. However, the association between GDF‐15 levels and MetS or its components in the non‐elderly subjects remains unclear. In this study, a total of 279 subjects younger than 65‐year‐old with (n = 84) or without (n = 195) MetS were recruited. MetS was defined according to modified NCEP/ATP III criteria. The GDF‐15 levels were measured by an enzyme‐linked immunosorbent assay. A multiple linear regression analysis was conducted to identify factors independently associated with GDF‐15 levels. Subjects with MetS had higher GDF‐15 levels than those without MetS (median (interquartile range), 1.72 ng/mL (1.38, 2.26) vs. 1.63 ng/mL (1.27, 2.07), P = 0.037). With the number of MetS components increased, the GDF‐15 levels increased significantly (P for trend = 0.005). Multiple linear regression analysis revealed that the presence of MetS was positively associated with the GDF‐15 levels (β = 0.132, P = 0.037). When substituting MetS with its components, only the presence of hyperglycemia was positively associated with the GDF‐15 levels after adjustment for covariates (β = 0.193, P = 0.003). Taken together, the presence of the MetS in non‐elderly was associated with higher GDF‐15 levels. Among the MetS components, only hyperglycemia was significantly associated with the GDF‐15 levels. Future longitudinal studies will be needed to explore whether GDF‐15 has the potential to be a biomarker of gluco‐metabolic dysfunction in non‐elderly subjects.